ELSUM's English language carnival blends learning, fitness, and public speaking - Jeri, Shirley Clare; Daneil, Imelia Laura; Joseph, Stefanie Natasha Rich; Robert, Cindy (Corporate Communication Unit, UiTM Mukah Campus, 2025)
The English Language Society of UiTM Mukah (ELSUM) successfully hosted its English Carnival, a dynamic programme designed to promote language learning through creative and engaging activities. The day began with a lively Zumba session, joined by over 30 participants and led by three student instructors. Set to English hits from the 1990s, the activity served as an energetic warm-up for the subsequent Fun Run. Following light refreshments, more than 50 participants took part in the run, completing six English-themed checkpoints, including “Guess the Idioms,” “Charades,” “Trivia,” and “Spelling Bee.” To add to the excitement, participants who answered incorrectly were playfully splashed with water, creating a spirited and memorable atmosphere.